Soil agrochemical and microbiological changes during leguminous forage grass cultivation in the southern steppe of Ukraine - Vlashchuk Anatoly; Valentiuk Nataliia; Kholmurodova Dilafruz (BIO Web of Conferences)
Increased use of arable land during the last century has led to a total decrease in soil fertility on the planet. Dehumification processes are activated in the absence of the supply of organic matter and unbalanced application of mineral fertilizers, ignoring crop rotations, minimizing the area of growing leguminous crops, burning straw in the soil. Therefore, the question of increasing the efficiency of agriculture and reproduction of soil fertility becomes urgent. The goal is to investigate the influence of leguminous forage grasses on changes in the agrochemical and microbiological composition of the soil under different methods of soil cultivation in irrigated and non-irrigated conditions. The research was carried out in the conditions of the Odesa region (Ukraine) during 2022- 2024 by the method of a three-factor experiment (factor A - the presence of irrigation; Factor B - the method of cultivation of hryvnia, Factor C - fodder leguminous grasses). It was established that the NO3 content decreased according to the experiment options during the vegetation period from 12.17-12.31 mg/100 g of soil to 9.97-10.19 mg/100 g of soil. The content of P2O5 decreased from 6.27-6.40 mg/100 g of soil to 5.02-5.23 mg/100 g of soil, which represents an average to high level of soil provision. Significant differences were not observed in the use of available potassium. The total number of microorganisms in 1 g of completely dry soil during the growing season increased from 24.89-25.09 million to 29.87-31.20 million. In the experiment variants where irrigation was used, the values of the indicator were slightly higher than in non-irrigated areas, which indicates the positive effect of irrigation on improving the microbiological composition of the soil. The introduction of ecologically safe leguminous fodder crops into crop rotations contributes to the improvement of agrocenoses in the crop rotation of organic farming and ensures the improvement of the ecological and phytosanitary condition of the soil.